Efficiency Analysis of Container Ports in Vietnam Using Stochastic Frontier Analysis - Thanh Uyen Bui; Gyu Sung Cho (한국해양공학회지, 2025)
This study compared the technical efficiency of container ports in Vietnam to pinpoint areas for improvement, enabling the ports to enhance their efficiency and competitiveness within the Vietnamese port industry. This analysis used cross-sectional data from 13 major container ports and terminals across the country, utilizing the variables related to port infrastructure, including the total quay length (in meters), maximum alongside depth (in meters), and total terminal area (in square meters). The output metric used was the cargo volume, measured in twenty-foot equivalent units (TEU) per year. The port efficiency was measured using stochastic frontier analysis (SFA), with the dataset sourced primarily from the official Vietnam Seaports Association website (www.vpa.org.vn). The methods were used to analyze the variations in port efficiency, including aspects such as distribution, rankings, identification of the best and worst ports, and determinants of the efficiency frontier. The results suggest that the port efficiency, as measured using the SFA models, enhances the technical efficiency scores of the container ports, with the collected scores generally being high among the 13 observations. This highlights the significance of the term error in container port production, showing that the seaport sector is an area where perception errors are highly developed. In addition, ports with higher throughput do not always have the highest efficiency scores. Therefore, the port authorities and managers responsible for port investment and management in Vietnam should consider using the SFA method to estimate and improve port efficiency.